2016
DOI: 10.1002/adem.201500604
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rate Sensitivity on Structural Sandwich Plates with Sinusoidal Corrugated Cores

Abstract: A plane strain elastic-viscoplastic-based finite element model is developed to simulate a composite system with sinusoidal corrugated cores under tensile loading conditions. Numerical study shows that the rate sensitivity in the reinforced core provides a positive impact on loading capacity, the necking strain retardation, and improvement in the ductility of a composite. By carefully selecting the reinforced sinusoidal core geometric parameters, extra margin can be gained in improving the uniform elongation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…It is clear that as the height of the corrugation is increased the necking strain of the composite increases, which agrees with what has been seen in the literature. [20,21,30] Looking at Figure 5b, which shows the work hardening curves for 20% volume fraction composites with different corrugation heights, it is clear that the boost in work hardening from the unbending of the corrugation becomes more prominent and is initiated at larger values of strain as the corrugation height is increased. This delay of the boost in work hardening, coupled with the more significant boost is what leads to samples with larger corrugation heights showing larger values of necking strain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear that as the height of the corrugation is increased the necking strain of the composite increases, which agrees with what has been seen in the literature. [20,21,30] Looking at Figure 5b, which shows the work hardening curves for 20% volume fraction composites with different corrugation heights, it is clear that the boost in work hardening from the unbending of the corrugation becomes more prominent and is initiated at larger values of strain as the corrugation height is increased. This delay of the boost in work hardening, coupled with the more significant boost is what leads to samples with larger corrugation heights showing larger values of necking strain.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting at this time that this study strictly focuses on a sinusoidal corrugated structure. This sinusoidal corrugated geometry is commonly used in the study of corrugated materials, [12][13][14]18,[21][22][23][24][25][26][27][28][29][30][31] however it is not the only corrugated geometry used and many other studies use trapezoidal corrugations, [15,19,20] and circular corrugations. [14][15][16] All of these corrugation geometries display similar increasing work hardening behavior when loaded in tension and the main difference between the geometries lies in the manner and location in which the unbending is focused, the amount of force required to unbend to a certain degree and the corresponding strain at which complete unbending has occurred.…”
Section: Modeling Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The necking strain of a material can be increased by introducing a wavy or corrugated reinforcement. There have been a number of studies that investigate the effect of a corrugated geometry on the behavior of isolated corrugations [ 1 , 2 , 3 , 4 , 5 , 6 ], sandwich panels with a corrugated core [ 7 , 8 , 9 ], and composites materials with corrugated reinforcements [ 3 , 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Dayyani et al [ 1 ] and Thill et al [ 2 ] both explored the behavior of isolated trapezoidal corrugated structures, whereas Bouaziz [ 3 ], Boke [ 4 ], Ge [ 5 ], and Fraser et al [ 6 ] studied and modeled the behavior of isolated sinusoidal corrugated structures.…”
Section: Introductionmentioning
confidence: 99%
“…In general, these studies have shown that when loaded in tension along the longitudinal direction, the corrugated structure shows a lower initial stiffness and lower strength level, followed by a hardening process as a result of the unbending of the corrugation. In some of the studies [ 3 , 4 , 6 , 13 , 21 , 23 ] where the deformation was taken to high levels of strain, this unbending process was shown to lead to a material that necks at a higher level of strain compared to an uncorrugated counterpart and yet still has a comparable ultimate tensile strength. This ability to improve necking strain, without sacrificing strength, can lead to promising combinations of properties, particularly for energy absorption applications.…”
Section: Introductionmentioning
confidence: 99%